PALINOLOGIA DA FORMACÁO SANTANA (CRETÁCEO DO NORDESTE DO BRASIL). III. DESCRICÁO SISTEMÁTICA DOS POLENS DA TURMA PLICATES (SUBTURMA COSTATES) (Ameghiniana, 2013)
The present paper represents the third of four parts, devoted to the palynology of the Cretaceous Santana Fonnation. Presented systematically here, are 52 specíes of polyplicate pollen grains,grouped in 5 genera, of whích one genus and eighteen species are new. The new descríbed taxa are: Regalipollenites n. g.; Equisetosporites subcircularis, Equisetosporites elegans, Equisetosporites fragilis, Equisetosporites leptomatus, Equisetosporiies minuticostatus, Equisetosporites luridus, Equisetosporites lanceolatus, Equisetosporites laticostatus, Singhia punctata, Singhía mínima, Singhia acicularis, Singhia reurei, Singhia crenulata, Gnetaceaepollenites vesuguii, Netaceaepollenites retangularis, Cnetaceaepollenites ornatus, Cnetaceaepolleniies perforatus and Cneta: ceaepollenites santosii.